Investigating the effect of intellectual computer games on creative thinking skills and increasing concentration in children of divorce - Sophia Khaneghahi; Afsaneh Pudineh; Mohammad Aref Mahmoud Zehi (Journal of Social, Humanity, and Education, 2022)
Purpose: The main purpose of this study is to investigate the effect of intellectual computer games on creative thinking skills and increase concentration in children of divorce. Research methodology: The statistical population of the study includes all single parent children 7 to 10 years old in Zahedan in the academic year 2021-2022. To select the research sample, first 40 people were available as a sample through cluster random sampling. Data collection tools in this study included a questionnaire. Results: Findings showed that intellectual computer games affect increasing creative concentration and thinking in children of divorce. Based on the findings, it can be stated that computer games are a mental and cognitive activity that leads children to reach high levels of thinking and increase their concentration and creative thinking. Limitations: One of the most important limitations of the present study is that due to the timing of the conference, researchers did not have enough time to conduct follow-up tests to sustain the impact of brain teasers. Contribution: Another use of mind games is in teaching and learning, especially for single parents and divorced children who have less concentration. Therefore, due to the high desire and tendency of children to computer games.